The camp of interned soldiers of the Army of the Ukrainian People's Republic in Aleksandriv, Poland in the spring and summer of 1921 (based on the materials of the Central State Archive of the Supreme Governance and Management of Ukraine) - Ihor Sribniak (Cхід, 2018)
Author puts into scientific use new historical data about domestic life of internee military man.  In particular, author analyzes the conditions of the interned Ukrainian warfare in the camp of Alexandriv (Poland) in the spring and summer of 1921. It is proved that the life of Ukrainian soldiers was marked by considerable difficulties, which was caused by unsanitary in the camp, not always a satisfactory diet and a general unfavorable regime for the maintenance of interned. All this led to the demoralization of the part of the interned Ukrainian battleship, which had no stable national-state feelings. Some of them left the camp unauthorized, after which such persons were excluded from the army of the UNR as deserters. But despite all the complexity of parts and connections kept their military organization, and thanks to well-organized work of the camp's hospital in the camp it was possible to prevent the spread of infectious diseases. All this time, the headquarters of the group effectively carried out organizational and managerial functions by all partis of the life and activities of the interned in the camp.